PENGARUH KUALITAS PRODUK DAN E COMMERCE TERHADAP KEPUASAN KONSUMEN PADA AZZAHRA CAKE DI KECAMATAN KINALI - Mai Yuliza; Wahyu Indah Mursalini; Almasdi Almasdi; Afniyeni Afniyeni; Nelnis Nelnis (JURNAL ILMIAH EDUNOMIKA, 2022)
The purpose of this study was to see the effect of product quality and e-commerce on consumer satisfaction. The population of this study were all consumers at Azzahra Cake kinali with a total sample of 100 people. Data were collected through questionnaires with assessment criteria using a Likert scale. The results showed that product quality had a positive and significant effect on consumer satisfaction with a coefficient value of 0.690 and a significance value of 0.000. E-Commerce has a positive and significant effect on consumer satisfaction with a coefficient value of 0.153 and a significance value of 0.039. And product quality and E-Commerce simultaneously have a positive and significant effect on consumer satisfaction with a significance value of 0.000. The coefficient of determination of 46.4% shows the effect of product quality and E-commerce on consumer satisfaction at Azzahra Cake is 46.4% while the remaining 53.6% is influenced by other factors that have not been studied in this study such as environmental factors, emotional intelligence and product prices. Keywords : Consumer Satisfaction, Product Quality And E_Commerce